2022
DOI: 10.3390/rs14164033
|View full text |Cite
|
Sign up to set email alerts
|

Projection of Future Extreme Precipitation in China Based on the CMIP6 from a Machine Learning Perspective

Abstract: In recent years, China has suffered from frequent extreme precipitation events, and predicting their future trends has become an essential part of the current research on this issue. Because of the inevitable uncertainties associated with individual models for climate prediction, this study uses a machine learning approach to integrate and fit multiple models. The results show that the use of several evaluation metrics provides better results than the traditional ensemble median method. The correlation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…For example, Xu et al (2019) used precipitation simulation from CMIP5 to investigate future precipitation extremes in China and reported that RX1day and RX5day show an increasing trend for the twenty‐first century under different scenarios, but the increase of RX1day is more obvious than RX5day. Yan et al (2022) found that RX5day is projected to increase in most areas of China with the largest relative changes in northwestern areas by the end of the 21st century (2076–2100) compared with the historical period (1990–2014), which is similar to our results for RX1day.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Xu et al (2019) used precipitation simulation from CMIP5 to investigate future precipitation extremes in China and reported that RX1day and RX5day show an increasing trend for the twenty‐first century under different scenarios, but the increase of RX1day is more obvious than RX5day. Yan et al (2022) found that RX5day is projected to increase in most areas of China with the largest relative changes in northwestern areas by the end of the 21st century (2076–2100) compared with the historical period (1990–2014), which is similar to our results for RX1day.…”
Section: Discussionsupporting
confidence: 91%
“…Locate FY-4A's cloud retrieval in the SWV coordinate system. For the SWV life stage with a specific time step, the cloud search results of all FY-4A pixels in the region are analyzed, and the cloud occurrence frequency (COF) of each type of cloud is calculated, as shown in Equation (1).…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Meteorologists have long been focused on understanding the formation, development, and flood disasters caused by this weather phenomenon. In recent years, in the context of global warming [1], extreme precipitation events triggered by the SWV have become more frequent, resulting in significant human and economic losses [2]. For example, from 7 to 11 July 2013, an extreme precipitation event in northern Sichuan registered a total precipitation of 415.9 mm, impacting 15 townships and 42,571 individuals [3].…”
Section: Introductionmentioning
confidence: 99%
“…China's coastal regions are thought to be sensitive and vulnerable to climate change, which could result in considerable losses from climate-related disasters because of the country's enormous population Yan et al, 2022b). Despite the substantial expected increase in precipitation in the coastal area of China, the Palmer Drought Severity Index is projected to indicate drier conditions.…”
Section: Precipitation Projection 361 Mean Annual Precipitation Changementioning
confidence: 99%